Why engage in co-production of public services? mixing theory and empirical evidence - Eijk, Carola Van; Steen, Trui (2016)
Through processes of co-production, citizens collaborate with public service agents in the provision of public services. Despite the research attention given to co-production, some major gaps in our knowledge remain. One of these concerns the question why citizens engage in processes of co-production of public services. In this article, a theoretical model is built that brings the human factor into the study of co-production. The model explains citizens engagement in co-production referring to citizens perceptions of the co-production task and of their competency to contribute to the public service delivery process, citizens individual characteristics, and their self-interested and community-focused motivations. Empirical evidence from four co-production cases in the Netherlands and Belgium is used to demonstrate the model's usefulness. The academic and practical relevance of the findings and suggestions for further research are discussed. - Reproduced.
Keywords: Public administration